Metabolism and biomarkers of Vitamin D - Jones, Glenville (Scandinavian journal of clinical & laboratory investigation. Supplement, 2012)
Abstract The last decade has witnessed a renaissance in the interest in the metabolism and biological actions of vitamin D3. Part of this new found interest stems from the discovery that its active form, 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], through its nuclear vitamin D receptor [VDR], regulates hundreds of genes around the body including those coding for proteins involved in cell differentiation and cell proliferation as well as calcium and phosphate homeostasis. Furthermore, epidemiological association studies have suggested that levels of the main circulating form, 25-hydroxyvitamin D3 [25(OH)D3] correlate positively with various health outcomes connected to major diseases: cancer, immune function and infections and cardiovascular disease. Consequently, the biochemistry around the metabolism of vitamin D, its mechanism of its action in target cells and the clinical chemistry questions regarding its specific and sensitive assay remain relevant. This short article will review the current state of knowledge of the cytochrome P450-enzymes involved in activation and inactivation of vitamin D, as well as provide a synopsis of the biochemistry and physiology surrounding its roles in the body. The review will end by discussing the appropriate biomarkers to assess vitamin D metabolism and vitamin D status in various clinical disease settings.